Метод решения задач ползучести тел на основе смешанного вариационного принципа - Морачковский, Олег Константинович; Соболь, Владимир Николаевич (НТУ "ХПИ", 2003)
General statement of creep problems of spatial bodies and variational principle for the mixed functional is given, which for knowing at the any time of moment creep deformations on independently varied functions of strains and stress are formulated. Numerical method for calculation of initially - edges creep problems of bodies is considered in which Runge-Kutta-Merson method and R-functions method are applied. Numerical data of research convergence of approximate solutions with using amount variation of free components in the solution structures and integration accuracy of creep condition equations on the calculation example of rotation bodies are presented
Keywords: высокотемпературная техника; параметр повреждаемости; фланцы